Design and performance of the APPLE‐Knot undulator. (8th June 2015) - Ji, Fuhao; Chang, Rui; Zhou, Qiaogen; Zhang, Wei; Ye, Mao; Sasaki, Shigemi; Qiao, Shan
<x xml:space="preserve">Abstract</x> Along with the development of accelerator technology, synchrotron emittance has continuously decreased. This results in increased brightness, but also causes a heavy heat load on beamline optics. Recently, optical surfaces with 0.1 nm micro‐roughness and 0.05 µrad slope error (r.m.s.) have become commercially available and surface distortions due to heat load have become a key factor in determining beamline performance, and heat load has become a serious problem at modern synchrotron radiation facilities. Here, APPLE‐Knot undulators which can generate photons with arbitrary polarization, with low on‐axis heat load, are reported.